Identifying Opportunities for Inpatient-Centric Technology - Skeels, Meredith; Tan, Desney (IHI '10 Proceedings of the 1st ACM International Health Informatics Symposium, 2010)
The evolution from a disease-centered model of care to a more patient-centered model presents opportunities for going beyond designing technology to support medical professionals to encompass supporting patients as well. In this work, we conducted interviews with 16 inpatients and 5 visitors in several hospital wards to uncover opportunities for improving the inpatient experience. Findings suggest that a redesign of the call button system could improve nurse-patient communication and relieve anxiety. Providing information about overall progress and upcoming events could help patients maintain a sense of autonomy in a disempowering environment. Helping patients learn more about their health through information access could lead to a greater sense of ownership over health. Technology promoting social connectedness could help patients virtually escape the isolating hospital environment. Finally, novel interaction techniques could make technology more accessible to this unique population.